The liberation of Marguerite Harrison : America's first female foreign intelligence agent - Atwood, Elizabeth Ann (Naval Institute Press, 2020)
"In September 1918, World War I was nearing its end when Marguerite E. Harrison, a thirty-nine-year-old Baltimore socialite, wrote to the head of the U.S. Army's Military Intelligence Division asking for a job. The director asked for clarification. Did she mean a clerical position? No, she told him. She wanted to be a spy. Harrison, a member of a prominent Baltimore family, usually got her way. She had founded a school for sick children and wangled her way onto the staff of the Baltimore Sun. Fluent in four languages and knowledgeable of Europe, she was confident she could gather information for the U.S. government. The MID director agreed to hire her, and Marguerite Harrison became America's first female foreign intelligence officer."--